Can a transboundary multistakeholder platform support growing water cooperation in the Incomati Basin? - Nehring, Ryan; Mgudlwa, Maliviwe; Mswane, Edward; Fakudze, Buyani; Sibia, Oscar; Mthimkhulu, Sindy; Machimana, Sylvia; Lautze, Jonathan F. (CGIAR, 2023)
The Incomati River is one of 15 major transboundary basins in Southern Africa. Shared by Eswatini, Mozambique and South Africa, the basin is highly developed and has substantial flow-regulating infrastructure such as weirs and large dams. Key among these are the Maguga Dam in Eswatini and Driekoppies Dam in South Africa, which both provide water for irrigated crops such as sugar cane. Maguga is also used to generate hydropower.